(3CUhd GdbjGS GdeMGSHj s - (3fHjd(B, (3GdMdHjs; (3HWQS ejGdI(B, (3eMehO Ydj GdLHGdjs ((3GQHO(B:s (3OGQ GdCed(B,s, 1998)
(3GdCUhd GdKGHJI hGdJShjGJ GdLQOjI,GdeNRhf GdSdYj(B((3GdHVGYI(B)(3hGdJShjGJ GdLQOjI,GdeOjfhf hChQGb GdbHV hGdJShjGJ GdLQOjI,GdGdJRGeGJ hGdJShjGJ GdLQOjI,GdJShjGJ GdLQOjI dMSGHGJ GdeUQhaGJ hGdEjQGOGJ,GdbhGFe GdeGdjI GdNJGejI,GdYdGbI Hjf GdeMGSHI hGdMGShHs
(3HjHdjhZQGajG U(B.299s
Keywords: (3GdeMGSHIs